Improving the election law in Vietnam - Phan, Van Ngoc (Đại học Quốc Gia Hà Nội, 2020)
The Election Law is an integral part of the constitution law. In each country, the Election Law has its own characteristics without a common electoral model. Even the Nation’s Election Law has also changed from time to time. The Election Law in Vietnam can be divided into three stages with different characteristics, reflecting the Party’s views, the Vietnamese State’s policies on the People’s power, the democracy practice mechanism and the requirements to build and to improve the State apparatus. Since 1992, the Election Law has gradually changed fundamentally in response to the demands of domestic political and legal practice and international integration. The enactment and adoption of the 2013 Constitution and the Election Law 2015 marked a new milestone in the development of the Election Law, showed a new and deeper spirit and awareness of human rights, the civil rights, the People’s sovereignty, the democracy and democratic practice mechanism, building the socialist rule of law State of the People, by the People and for the People. However, the Election Law still has limitations and shortcomings before the profound changes in socio-political life after more than 30 years of conducting the Doi Moi (Reforms).